JNK Signaling Pathway Activity Alterations in the Rat Hippocampus: Effect of Age, Alzheimer’s Disease-Like Pathology Development, and the JNK Inhibitor IQ-1S; Biochemistry (Moscow); Vol. 90, iss. 2 - Muraleva N. A. Natalia; Zhdankina A. A. Anna Alexandrovna; Khlebnikov A. I. Andrey Ivanovich; Kolosova N. G. Natalia Gorislavovna (2025, 2025)
Title screen